Effectiveness of federal education funding on rural schools: A quantitative study - Melissa Beck Wells (Educational Futures)
This study examines the influence of federal education funds on educational outcomes in US rural schools, with a particular focus on student performance, attendance rates, and teacher retention. Utilizing a sample from the National Center for Rural Education Research Networks and other federal databases, the study evaluates fiscal allocations from the US Department of Education’s 2024 budget to assess rural schools’ unique challenges and needs. Findings suggest that, while funding impacts certain operational metrics, the effect on student outcomes is less direct, underscoring the need for targeted intervention strategies.